Is It Best to Have It All: Emotional, Cognitive and Behavioral Consequences of Conflicting Expert Advice on Decision Makers - Chang, Xiaoxi (Université d'Ottawa / University of Ottawa, 2014)
Whether it is in private or professional lives, people are called to make decisions and they tend to seek expert advice. The old adage indicates that more heads are better than one. Receiving more information is often helpful to decisions. However, getting multiple conflicting expert advice might put decision makers in difficult situations. Little is known about their feelings, thinking, and behaviors under such conditions. This research aims to fill the gap and understand the abovementioned consequences of taking multiple conflicting expert advice when making professional (i.e., business or personnel-related) decisions. Using an interview-based qualitative approach, this research sheds light on contextual characteristics where conflicting expert advice may be more beneficial (or harmful), which contributes practical recommendations to improve professional decisions. In sum, this research seeks to verify whether the common wisdom of “more is better” holds up to empirical scrutiny, and suggests that it is “no pain, no gain”.
Keywords: Professional Decision Making; Expert Advice Taking; Conflicting Advice Taking; Emotional Outcome; Cognitive Outcome; Behavioral Outcome